Bioavailability of epicatechin and effects on nitric oxide metabolites of an apple flavanol‐rich extract supplemented beverage compared to a whole apple puree: a randomized, placebo‐controlled, crossover trial. Issue 7 (23rd April 2013) - Hollands, Wendy J.; Hart, David J.; Dainty, Jack R.; Hasselwander, Oliver; Tiihonen, Kirsti; Wood, Richard; Kroon, Paul A.
Abstract : Scope: Flavanol‐rich foods are known to exert beneficial effects on cardiovascular health. The biological effects depend on bioavailability of flavanols which may be influenced by food matrix and dose ingested. We compared the bioavailability and dose‐response of epicatechin from whole apple and an epicatechin‐rich extract, and the effects on plasma and urinary nitric oxide (NO) metabolites. Methods and results: In a randomized, placebo‐controlled, crossover trial, subjects consumed drinks containing 70 and 140 mg epicatechin from an apple extract and an apple puree containing 70 mg epicatechin. Blood and urine samples were collected for 24 h post ingestion. Maximum plasma concentration, AUC(0–24 h), absorption and urinary excretion were all significantly higher after ingestion of both epicatechin drinks compared with apple puree ( p < 0.05). Time to maximum plasma concentration was significantly later for the puree compared with the drinks ( p < 0.01). Epicatechin bioavailability was >2‐fold higher after ingestion of the 140 mg epicatechin drink compared to the 70 mg epicatechin drink ( p < 0.05). Excretion of NO metabolites was higher for all test products compared with placebo, which was significant for the high dose drink ( p = 0.016). Conclusions: Oral bioavailability of apple epicatechin increases at higher doses, is reduced by whole apple matrix and has the potential to increase NO bioavailability.